A new strategy to prepare n-HA/CS composite scaffolds with surface loading of CS microspheres. Issue 16 (2nd November 2022) - Lin, Mingyue; Zou, Qin; Wang, Chenxin; Zhang, Rui; Li, Yufan; Li, Taihe; Li, Yubao
Abstract: A nano-hydroxyapatite/chitosan (n-HA/CS) scaffold loading with CS microspheres was developed in this study. First, CS microspheres with an average diameter of ∼57 μm were prepared by cross-linking, and a three-dimensional (3D) printing technology was used to fabricate n-HA/CS porous scaffolds with an average pore size and porosity of 454 ± 51 μm and 60.71%, respectively. Then, the n-HA/CS scaffolds were immersed in a solution of CS microspheres and cross-linked by vanillin. The structure, porosity, composition, and cellular behavior of the CS-microsphere-loaded scaffolds were investigated. In vitro cell experiments showed that the CS microspheres on the scaffolds could effectively promote the adhesion and growth of cells on the scaffolds, suggesting that the CS microspheres and the scaffolds have good cytocompatibility. The composite scaffolds were implanted in the back muscles of rabbits for 3, 6, and 9 weeks, and the results of subsequent SEM and H&E staining analyses demonstrated that both the n-HA/CS scaffolds and the loaded CS microspheres had good biocompatibility and gradually degraded over time, where the microspheres were gradually released from the scaffolds. The strategy developed in this study for loading microspheres on scaffolds has promising prospects for future clinical applications of enhancing bone defect repair or implant integration. Graphical Abstract: UF0001